Short-Term High-Fat Diet Fuels Colitis Progression in Mice Associated With Changes in Blood Metabolome and Intestinal Gene Expression - Wu, Zhen-Hua; Yang, Jing; Chen, Lei; Du, Chuang; Zhang, Qi; Zhao, Shan-Shan; Wang, Xiao-Yu; Yang, Jing; Liu, Yang; Cai, Demin; Du, Jian; Liu, Hui-Xin (Frontiers in Nutrition, 2022)
Clinical cases and animal experiments show that high-fat diet (HF) involved in inflammatory bowel disease (IBD), but the specific mechanism is not fully clear. A close association between long-term HF-induced obesity and IBD has been well-documented. However, there has been limited evaluations of the impact of short-term HF feeding on the risk of intestinal inflammation, particularly on the risk of disrupted metabolic homeostasis. Here, we analyzed the metabolic profile and test the Vulnerability of 2,4,6-trinitrobenzenesulfonic acid (TNBS) induced colitis after short-term HF feeding in mice. The results showed that compared with the control diet (CD), the fatty acids (FAs), amino acids (AAs) and bile acids (BAs) metabolism of mice in the HF group were significantly changed. HF-fed mice showed an increase in the content of saturated and unsaturated fatty acids, and a decrease in the content of tryptophan (Trp). Furthermore, disturbed spatial distribution of taurocholic acid (TCA) in ileum and colon were identified in HF group by using matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI). After HF priming, mice on TNBS induction subjected to more severe colonic ulceration and histological damage compared to the CD counterparts. In addition, TNBS enema induced higher gene expressions of mucosal pro-inflammatory cytokines under HF priming condition. Overall, our results show that HF may promotes colitis by disturbing lipid, AAs and BAs metabolic homeostasis and inflammatory gene expressions.